2023
DOI: 10.1038/s41598-023-28508-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined space stressors induce independent behavioral deficits predicted by early peripheral blood monocytes

Abstract: Interplanetary space travel poses many hazards to the human body. To protect astronaut health and performance on critical missions, there is first a need to understand the effects of deep space hazards, including ionizing radiation, confinement, and altered gravity. Previous studies of rodents exposed to a single such stressor document significant deficits, but our study is the first to investigate possible cumulative and synergistic impacts of simultaneous ionizing radiation, confinement, and altered gravity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Previously, in open field, Raber et al observed that females had higher activity levels than males, but for all doses and sham exposures [ 18 ], where Lui et al found male mice were more susceptible to radiation-induced changes in activity levels than female mice after 10 or 50 cGy exposure of 56 Fe [ 37 ]. Rienecker et al did not observe any dose or sex differences in the time spent in the center of the open field arena [ 21 ]. Here, both males and females spent more time moving at the delayed timepoint than acute, regardless of dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, in open field, Raber et al observed that females had higher activity levels than males, but for all doses and sham exposures [ 18 ], where Lui et al found male mice were more susceptible to radiation-induced changes in activity levels than female mice after 10 or 50 cGy exposure of 56 Fe [ 37 ]. Rienecker et al did not observe any dose or sex differences in the time spent in the center of the open field arena [ 21 ]. Here, both males and females spent more time moving at the delayed timepoint than acute, regardless of dose.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there was a trend toward an effect of radiation where BDNF levels increased in the cortex of males but not females [ 19 ]. Rienceker et al (2023) observed behavioral deficits and elevated peripheral blood monocytes and Natural Killer cells in group-housed males but not females, after exposure to 50 cGy 5-ion GCRSim [ 21 ]. Given the sexually dimorphic nature of the behavioral responses, establishing a GCRSim dose–response curve is key to enabling the selection of a dose that evokes a midrange response in future studies of both sexes to avoid ceiling or floor effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the findings from these studies can contribute to addressing disturbances that may arise during spaceflights involving organisms [9]. Thus, it is essential to analyze the behavior of different species and cells under hypergravity conditions and evaluate any resultant changes to identify potential beneficial applications [10], [11]. To accomplish this, the changes can be monitored within a container equipped with an array of cameras, enabling subsequent image processing and analysis [12].…”
Section: Introductionmentioning
confidence: 99%